2018
DOI: 10.1177/1934578x1801300913
|View full text |Cite
|
Sign up to set email alerts
|

Italian Lycium barbarum L. Berry: Chemical Characterization and Nutraceutical Value

Abstract: Lycium barbarum L. has received considerable attention in recent years also in western countries because of the interesting healthy value of these berries. In this paper, goji samples cultivated in Southern Italy were analyzed for their chemical composition and nutritional profile in order to characterize fruits of Italian origin and to increase the awareness about their nutraceutical value. Lipid fraction was characterized by high percentages of unsaturated fatty acids, in particular oleic and linoleic acids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
(56 reference statements)
2
18
1
Order By: Relevance
“…The most abundant fatty acids were linoleic (C18:2n-6), oleic (C18:1n-9), palmitic (C16:0), and stearic (C18:0) acid, accounting for about 95% of total fatty acids. Similar results were reported for red goji berry cultivated in Italy [40,41], Greece [42], Turkey [43], North Macedonia [44] and for Chinese black goji berries [24,45]. Table 2.…”
Section: Red Goji Yellow Goji Black Gojisupporting
confidence: 84%
See 2 more Smart Citations
“…The most abundant fatty acids were linoleic (C18:2n-6), oleic (C18:1n-9), palmitic (C16:0), and stearic (C18:0) acid, accounting for about 95% of total fatty acids. Similar results were reported for red goji berry cultivated in Italy [40,41], Greece [42], Turkey [43], North Macedonia [44] and for Chinese black goji berries [24,45]. Table 2.…”
Section: Red Goji Yellow Goji Black Gojisupporting
confidence: 84%
“…The red goji berries contained 15.7% of the RDA for iron and could be recommended as a source of this valuable microelement. In this study, the iron content in red goji berry was about 5-fold higher than found in fresh red goji berries of Italian origin [38,41].…”
Section: Red Gojimentioning
confidence: 78%
See 1 more Smart Citation
“…The TPC of 5906 ± 1262 mg GAE/kg in Macedonian Goji berry was not significantly different from 6220 mg GAE/kg in Lycium chinense M. (p > 0.05). TPC in Goji of Macedonian origin was lower than in selected Goji cultivars in Romania (11600-15700 mg GAE/kg) [12], higher than in Goji cultivars in Switzerland (710-2940 mg GAE/kg) [11] and Italian Goji (7600 mg GAE/kg) [49]. The differences could be attributed to ecophysiological conditions, altitude and soil composition.…”
Section: Antioxidant Capacity Polyphenol and Carotenoid Profilesmentioning
confidence: 75%
“…The Goji fruit, also known as the wolfberry or Goji berry, is the main product commercialized as health food. Goji berry contains high amount of functional components, including sugars [3], carotenoids [4], and essential fatty acids [5].The polysaccharides extracted from wolfberries contain high antioxidative properties and have the ability to treat and prevent multiple chronic diseases, including cancer, diabetes, atherosclerosis, and male infertility [6][7][8][9]. The root bark of Goji (Lycii Radicis Cortex) has been used in treating hypertension and reducing serum glucose and lipids [10][11][12].…”
Section: Introductionmentioning
confidence: 99%